Juvenile Delinquency Problems in “Pumped up Kicks” Song's Lyrics - Salsabila, Shifa; Elis Fitriani; Cindya Risma Oktafia; Khoiriyatun Nisa’; Salsa Maya Adelia; Windy Ikaluny (English Journal Antartika, 2023)
Social issues often happen in everyone’s life. Not only happened in the movies, but it also happened in our real life. Some people tell it through lyrics and make it into a song, just like the problems researchers have found in the lyrics of the ‘Pumped up Kicks’ song. This study aims to address one of the social issues, namely juvenile delinquency, in the lyrics of the “Pumped up Kicks” song. The method used to analyze the juvenile delinquency in "Pumped up Kicks" song's lyrics involves descriptive, examining the lyrics, and interpreting their symbolic meanings. Researchers use the theory from Stuart Hall, which is the constructionist representation. This study examines how the song portrays themes of youth violence and the consequences of neglect. Through the lens of cultural studies, we dissect the song's lyrics to understand their reflection of broader cultural norms, values, and anxieties. The study showed that the juvenile delinquency revealed in the song’s lyrics is a minor who is struggling with mental health issues and homicidal thoughts, school violence, and gun violence in teenagers. In conclusion, this research aims to increase knowledge and bring awareness to the issues of teenagers, something that we have been hearing more and more about in the news at the time.